Search for ReCQL4 mutations in 39 patients genotyped for suspected Rothmund–Thomson/Baller‐Gerold syndromes. (26th March 2014) - Piard, J.; Aral, B.; Vabres, P.; Holder‐Espinasse, M.; Mégarbané, A.; Gauthier, S.; Capra, V.; Pierquin, G.; Callier, P.; Baumann, C.; Pasquier, L.; Baujat, G.; et al.
<x xml:space="preserve">Abstract</x> Three overlapping conditions, namely Rothmund–Thomson (RTS), Baller‐Gerold (BGS) and RAPADILINO syndromes, have been attributed to RECQL4 mutations. Differential diagnoses depend on the clinical presentation, but the numbers of known genes remain low, leading to the widespread prescription of RECQL4 sequencing. The aim of our study was therefore to determine the best clinical indicators for the presence of RECQL4 mutations in a series of 39 patients referred for RECQL4 molecular analysis and belonging to the RTS (27 cases) and BGS (12 cases) spectrum. One or two deleterious RECQL4 mutations were found in 10/27 patients referred for RTS diagnosis. Clinical and molecular reevaluation led to a different diagnosis in 7/17 negative cases, including Clericuzio‐type poikiloderma with neutropenia, hereditary sclerosing poikiloderma, and craniosynostosis/anal anomalies/porokeratosis. No RECQL4 mutations were found in the BGS group without poikiloderma, confirming that RECQL4 sequencing was not indicated in this phenotype. One chromosomal abnormality and one TWIST mutation was found in this cohort. This study highlights the search for differential diagnoses before the prescription of RECQL4 sequencing in this clinically heterogeneous group. The combination of clinically defined subgroups and next‐generation sequencing will hopefully bring to light new molecular bases of syndromes with poikiloderma, as well as BGS without poikiloderma.